Reactions of selected bean accessions to infection by Macrophomina phaseolina - Pastor Corrales, Marcial A.; Abawi, G.S. (Scientific Societies, 1988)
Fifty-three bean (Phaseolus vulgaris) accessions were evaluated for their reactions to infection by Macrophomina phaseolina under field and greenhouse conditions. A field nursery was established on an experimental farm near Santander de Quilichao, Colombia. All accessions were evaluated in paired rows, with and without inoculation, arranged in a randomized block design with three replicates. Field inoculations were made by placing 4 g of whole rice seeds colonized by M. phaseolina per 2-m row on top of the bean seeds in the open furrow. The accessions that showed resistant and intermediate reactions to M. phaseolina and appropriate controls totaling 36 entries were reevaluated in a similar nursery on the same farm. The materials included in the second nursery plus other accessions for a total of 49 also were evaluated in the greenhouse. Bean seeds were covered with 150 ml (layer 2 3 cm) of pasteurized soil infested with dried sclerotia of M. phaseolina (2 g/kg soil). Results of the field evaluation were similar to those obtained from the greenhouse. Twenty-two and 15 accessions were classified as resistant (disease severity rating [DSR] = 1 3) and intermediate (DSR = 3.1 6.0), respectively, following the CIAT evaluation scale of 1 (no visible symptoms) to 9 (plants dead). Among the highly resistant accessions were A 300, BAT 85, BAT 332, BAT 477, BAT 1385, BAT 1651, IPA 1, San Cristobal 83, EMP 86, and G 5059 (H6 Mulatinho). A 70, A 464, A 294, Rio Tibagi, and ICA Pijao were among the most susceptible to M. phaseolina. Based on these data, an international bean nursery consisting of 40 accessions was established and is available for evaluation against M. phaseolina in different bean production areas.